PENGARUH OPINI AUDIT, UKURAN PERUSAHAAN DAN PPROFITABILITAS TERHADAP AUDIT DELAY PADA SEKTOR INDUSTRI DASAR DAN KIMIA - Dewi Zulvia; Sisi Susanti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
Audit delay is the number of days required b the auditor to complete the audit work, which is measured from the closing date of the financial year to the date of issuance of the audited financial statements. In the basic and chemical industry sector in idx 2016-2020. Based on porousive sampling, the number of basic and chemical industrial companies used in this study were 9 copanies. hypothesisi testing using panel date regression using the eviews 8.0 program. The results of this study indicate that audit opinion has a positive and significant effect on audit delay, firm size has no effect on audit delay and profitability has no effect on audit delay